JIEE 2018
DOI: 10.23860/jiee.2018.01.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Global Engineering Course on Student Cultural Intelligence and Cross-Cultural Communication

Abstract: Cultural intelligence has been referred to using many different terms, including global competence, intercultural sensitivity, and cross-cultural communication. In our study we use Ang et al.'s (2007) definition for this construct: "an individual's capability to function and manage effectively in culturally diverse settings" (p. 336). Although several models have been developed to describe this concept (e.g., Bennett, 1986; King & Baxter Magolda, 2005), there are commonalities between them. Many of these model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Second, it is possible that changes in the assignment content throughout the course presented more opportunities for students to explore international challenges independently and therefore may have peaked their interests and awareness. In either case, these findings indicate that we were able to provide experiences that improved students' global engineering competency without traveling, supporting earlier work on this topic but extending it to learning in a virtual environment (e.g., Davis & Knight, 2018;Render et al, 2017;Soria & Troisi, 2014).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Second, it is possible that changes in the assignment content throughout the course presented more opportunities for students to explore international challenges independently and therefore may have peaked their interests and awareness. In either case, these findings indicate that we were able to provide experiences that improved students' global engineering competency without traveling, supporting earlier work on this topic but extending it to learning in a virtual environment (e.g., Davis & Knight, 2018;Render et al, 2017;Soria & Troisi, 2014).…”
Section: Discussionsupporting
confidence: 79%
“…Consequently, it is essential to explore opportunities for students to develop global competence on their home campus through extracurricular activities (Soria & Troisi, 2014), cultural simulations (Davis et al, 2019), or collaborative online international learning (Ogden & Ogna, 2020), among others. Prior work has suggested that students can develop global competence through traditional courses focused on global topics (Davis & Knight, 2018;Kinoshita et al, 2016), but less research has focused on virtual global learning experiences. If such experiences can be designed effectively, they have the potential to open access to global learning to students who might otherwise be unable to participate.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of the authors' knowledge, the use of CQ across engineering education studiesand indeed, across the STEM education literature-is extremely limited, and thus a potential tool for understanding how to enhance students' cultural capital to effectively work in global environments remains unexploited (Davis and Knight (2018)). Herein, we report for the first time a complete characterisation and analysis of the cultural intelligence of a large, diverse final-year BEng Chemical Engineering cohort by means of a validated cultural intelligence scale protocol (CQS) to assess the following research question: What are the most significant demographic characteristics that correlate with the level of cultural intelligence of undergraduate chemical engineering students?…”
Section: Introductionmentioning
confidence: 99%
“…Shared experiences with family can make it easier to reflect after a course is over, which is key to a successful study-abroad. 2 However, these observations may not generalize to post-pandemic online offerings. Due to the societal impacts of the pandemic, students are currently spending more time with their families than with fellow students.…”
Section: Reflectionmentioning
confidence: 99%